Biaxial strain modulated the electronic structure of hydrogenated 2D tetragonal silicene. Issue 72 (19th December 2019) - Tu, Haoran; Zhang, Jing; Guo, Zexuan; Xu, Chunyan
Abstract : Hydrogenation can open the band gap of 2D tetragonal silicene, α-SiH is semiconductors with a direct band gap of 2.436 eV whereas β-SiH is indirect band gap of 2.286 eV. The band gap of α-SiH, β-SiH and γ-SiH can be modulated via biaxial strain. Abstract : Silicene-based materials have attracted great attention due to their easier incorporation into silicon-based devices and components. In addition to the reported hydrogenated 2D tetragonal silicene (γ-SiH), we propose two stable atomic configurations of hydrogenated 2D tetragonal silicene (α-SiH and β-SiH) based on first-principles calculation. The calculated results indicate hydrogenation can effectively open the band gap of 2D tetragonal silicene, α-SiH is a semiconductor with a direct band gap of 2.436 eV whereas β-SiH is indirect band gap of 2.286 eV. We also find that the electronic band structure of α-SiH, β-SiH and γ-SiH can be modulated via biaxial strain. By applying biaxial strain in the range of −10% to 12%, the band gap of α-SiH, β-SiH and γ-SiH can be tuned in a range of 1.732–2.585 eV. Furthermore, direct–indirect or indirect–direct transition can be induced under biaxial strain, showing a high degree of flexibility in electronic band structure. The research not only broadens the diversity of hydrogenated 2D tetragonal silicenes, but also provides more possibilities of their applications in spintronic devices.